Allopathic and traditional health practitioners: A reply to Nemutandani, Hendricks and Mulaudzi - Rudi W. de Lange (AOSIS, 2017)
An earlier paper in this journal reported on the perception and experience of 77 allopathic health practitioners (AHPs) and health managers about working together with South African traditional health practitioners (THPs). The paper stated that the abolishment of the Witchcraft Suppression Act of 1957 and the introduction of the Traditional Health Practitioners Act No. 22 of 2007 is a milestone in the development of traditional health knowledge, and for the eventual incorporation thereof into modern health care practices. The authors also comment that a decolonisation of mindset and a change of attitude is required to change one's perception of traditional healer practices and to develop them parallel to allopathic health practice. This opinion paper is a response to the paper, to negate its claims about the Witchcraft Suppression Act of 1957 and to provide clarity on the Traditional Health Practitioners Act No. 22 of 2007 and related policies and regulations. Although this Act recognises THP, the Act and other regulations actually require THP to conform to practices analogous to those of AHP. It is rather a systematic and scientific 'mindset' that is required to develop THP parallel to AHP. The Traditional Health Practitioners Act of 2007 and the Draft Policy on African Traditional Medicine (TM) for South Africa dictate that a substantial THP sectoral transformation is required before there can be a parallel system. Legislation and regulations have excluded THP and African TM from operating (present and future) in the same space as AHP.